2020
DOI: 10.1093/infdis/jiaa194
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloides stercoralis Coinfection Is Associated With Greater Disease Severity, Higher Bacterial Burden, and Elevated Plasma Matrix Metalloproteinases in Pulmonary Tuberculosis

Abstract: Background Helminths and tuberculosis (TB) largely overlap at the population level. Whether helminth infections influence disease severity and bacterial burdens in TB is not well understood. Methods This study was conducted to examine the disease severity in a cohort of pulmonary TB (PTB) individuals with (Ss+) or without (Ss−) seropositivity for Strongyloides stercoralis infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Previous studies by our group and others [4, 33, 34] have confirmed a link between chronic helminth infection during TB infection and an increased Th2-type immune response with a concomitant impaired immune control of Mtb. In contrast, the impact of early helminth antigen exposure on host immunity against TB is largely unknown.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Previous studies by our group and others [4, 33, 34] have confirmed a link between chronic helminth infection during TB infection and an increased Th2-type immune response with a concomitant impaired immune control of Mtb. In contrast, the impact of early helminth antigen exposure on host immunity against TB is largely unknown.…”
Section: Discussionsupporting
confidence: 70%
“…On a similar scale, it has been estimated that up to one-third of the world’s population is infected with helminths and that TB and helminths overlap geographically, with 20–35% of people with TB being infected with helminths [2, 3] (WHO, 2017). Despite multiple studies showing an impact of helminths on cell-mediated immunity, there is yet limited evidence directly linking helminthic infections to the reactivation of latency or the impact on TB disease progression [4]. In fact, recent studies [5, 6] show that helminth exposure may also enhance immunity to mycobacteria and that there is a need to focus on the effects of specific helminth species and at different stages of Mtb infection.…”
Section: Introductionmentioning
confidence: 99%
“…Our main result is that human phagocytes had increased ability to control virulent Mtb during early stages of helminth exposure. Additionally, Ascaris lumbricoides or Schistosoma mansoni antigens showed differential effects on M1/M2 polarization markers of monocyte macrophages and cytokine expression, which indicated a gradual transition into a Th2-type immune response (25).…”
Section: Anti Ascrais Lumbricoides-iggmentioning
confidence: 98%
“…Moreover, hookworm infection in TB patients was associated with the therapeutic failure of anti-TB drugs [ 12 ], which could contribute to the increased prevalence of TB. Helminths such as Strongyloides stercoralis [ 13 ] and S . mansoni [ 14 ] infections also increased TB disease severity.…”
Section: Introductionmentioning
confidence: 99%